Análisis de registro de inventario del Comercial Tio Regalon de la ciudad de Babahoyo - Bedoya Medina, Melisa Marlene (2021)
The commercial Tío Regalón is a company dedicated to wholesale and retail activities of basic necessities such as the best-selling sugars, flours, fatty butters, among others. It was born in 2016 from the transition of Comercial Prieto recognized within the city of Babahoyo, with RUC 1206133025001 in the name of Ms. Reyna Prieto. The lack of inventory control is one of the setbacks to which the company is exposed due to the fact that it lacks an adequate record and control of the entries and exits of the inventory by the warehouse collaborators, which has compromised the satisfaction of customers because they do not have the availability requested, therefore, a shortage and dissatisfaction of the clientele begins to show, which in turn shows a deficiency in the control of the merchandise of the commercial "Tío Regalón, weakness that makes it difficult to reach the business goals. Due to the aforementioned, an analysis of the inventory record of the aforementioned commercial premises is made to better understand its lack of control of inventory systems and application of IAS 2.